Avoiding unfavourable outcomes in liposuction - Atul Khanna; George Filobbos (Indian Journal of Plastic Surgery)
The origin of liposuction can be traced to an adverse event by Dujarrier in 1921 when he used a uterine curette to remove fat from the knees of a ballerina ending in an amputation secondary to damage of the femoral artery. The history of liposuction since then has been one of avoiding complications and optimising outcome. After this adverse event, liposuction was abandoned until the 1960′s when Schrudde revived the practice using small stab incisions and sharp curettage with the secondary suction to aspirate the freed tissue. This technique was associated with a high incidence of complications especially seroma and skin necrosis. Illouz then replaced the curette with a blunt cannula connected to vacuum pump thus avoiding the complications of a sharp curette. Despite the presence of various techniques for liposuction, suction assisted liposuction (SAL) is still the standard technique of liposuction. This article aims to discuss literature regarding the various aspects of liposuction (SAL) and to highlight the salient points in the literature and in the senior author′s experience in order to avoid unfavourable outcomes in liposuction. A literature review on avoiding complication is in liposuction including some of the seminal papers on liposuction. Liposuction is generally a safe procedure with reproducible outcome. Just like any surgical procedure it should be treated with the utmost care. Illouz published 10 commandments for liposuction in 1989 and we review these commandments to demonstrate how liposuction has evolved.